Antibacterial mouthwash to prevent sexually transmitted infections in men who have sex with men taking HIV pre-exposure prophylaxis (PReGo): a randomised, placebo-controlled, crossover trial. Issue 5 (May 2021) - Van Dijck, Christophe; Tsoumanis, Achilleas; Rotsaert, Anke; Vuylsteke, Bea; Van den Bossche, Dorien; Paeleman, Elke; De Baetselier, Irith; Brosius, Isabel; Laumen, Jolein; Buyze, Jozefien; Wouters, Kristien; Lynen, Lutgarde; et al.
Summary: Background: Bacterial sexually transmitted infections (STIs) are highly prevalent among men who have sex with men who use HIV pre-exposure prophylaxis (PrEP), which leads to antimicrobial consumption linked to the emergence of antimicrobial resistance. We aimed to assess use of an antiseptic mouthwash as an antibiotic sparing approach to prevent STIs. Methods: We invited people using PrEP who had an STI in the past 24 months to participate in this single-centre, randomised, double-blind, placebo-controlled, AB/BA crossover superiority trial at the Institute of Tropical Medicine in Antwerp, Belgium. Using block randomisation (block size eight), participants were assigned (1:1) to first receive Listerine Cool Mint or a placebo mouthwash. They were required to use the study mouthwashes daily and before and after sex for 3 months each and to ask their sexual partners to use the mouthwash before and after sex. Participants were screened every 3 months for syphilis, chlamydia, and gonorrhoea at the oropharynx, anorectum, and urethra. The primary outcome was combined incidence of these STIs during each 3-month period, assessed in the intention-to-treat population, which included all participants who completed at least the first 3-month period. Safety was assessed as a secondary outcome. This trial is registered with Clinicaltrials.gov, NCT03881007 . Findings: Between April 2, 2019, and March 13, 2020, 343 participants were enrolled: 172 in the Listerine followed by placebo (Listerine-placebo) group and 171 in the placebo followed by Listerine (placebo-Listerine) group. The trial was terminated prematurely because of the COVID-19 pandemic. 151 participants completed the entire study, and 89 completed only the first 3-month period. 31 participants withdrew consent, ten were lost to follow-up, and one acquired HIV. In the Listerine-placebo group, the STI incidence rate was 140·4 per 100 person-years during the Listerine period, and 102·6 per 100 person-years during the placebo period. In the placebo-Listerine arm, the STI incidence rate was 133·9 per 100 person-years during the placebo period, and 147·5 per 100 person-years during the Listerine period. We did not find that Listerine significantly reduced STI incidence (IRR 1·17, 95% CI 0·84–1·64). Numbers of adverse events were not significantly higher than at baseline and were similar while using Listerine and placebo. Four serious adverse events (one HIV-infection, one severe depression, one Ludwig's angina, and one testicular carcinoma) were not considered to be related to use of mouthwash. Interpretation: Our findings do not support the use of Listerine Cool Mint as a way to prevent STI acquisition among high-risk populations. Funding: Belgian Research Foundation - Flanders (FWO 121·00).